2013
DOI: 10.18785/goms.3101.03
|View full text |Cite
|
Sign up to set email alerts
|

Age and Growth of the Sandbar Shark (Carcharhinus plumbeus) from the Northern Gulf of Mexico and the Western North Atlantic Ocean

Abstract: Age and growth analysis of the sandbar shark, Carcharhinus plumbeus, from the northern Gulf of Mexico and western North Atlantic Ocean was completed with vertebral samples (n = 1,194). Three parameter von Bertalanffy growth curves were run for male and female sandbar sharks separately, and growth parameters were estimated: theoretical maximum length (L ' ) = 172.9 ± 1.3 cm straight-line fork length [FL], growth coefficient (k) = 0.15 ± 0.01 yr 21 , x-intercept (t 0 ) = 22.3 ± 0.2 SE (male); and L ' = 181.2 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Additional samples were also collected from a fishery-independent gill-net survey in order to obtain juvenile Blacktip Sharks not captured by commercial vessels (Figure 1). A full description of the gear and fishing methods can be found in Hale and Baremore (2010).…”
Section: Methodsmentioning
confidence: 99%
“…Additional samples were also collected from a fishery-independent gill-net survey in order to obtain juvenile Blacktip Sharks not captured by commercial vessels (Figure 1). A full description of the gear and fishing methods can be found in Hale and Baremore (2010).…”
Section: Methodsmentioning
confidence: 99%
“…However, estimated thresholds may not necessarily align with age classes. For example, the estimated size categories for sandbar sharks aligned well with age groups (small; <1.11, medium; 1.11–6.93, large; >6.93 years) but not for blacktip sharks (small; <0.6, large; >0.6 years) based on von Bertalanffy growth model parameters for sexes combined (Deacy & Moncrief‐Cox, 2019; Hale & Baremore, 2014). Limited research has been conducted on whether shifts in habitat utilization occur at specific ages for shark species (Grubbs, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The difference in average length between the two studies could be due to a smaller sample size in the current study, which may result from fisheries bias. However, this difference could also indicate a lack of older fish in the population (Hale & Baremore, 2013) and in the sample. In a study conducted by Kurniawan et al (2021) in Indonesian waters, similar findings were observed, including a right-skew in the length frequency distribution.…”
Section: Size Compositionmentioning
confidence: 93%